Financial capability for wellbeing: An alternative perspective from the capability approach - Silvia Storchi; Susan Johnson (University of Bath, Centre for Development Studies (CDS), 2016)
Financial inclusion is about increasing the set of financial service options available and the concept of financial capability seeks to capture the idea that their effective use will lead to improved wellbeing. Studies on financial capability have so far adopted an ontological assumption that financial capability is a set of "optimal" financial behaviours which can be defined and measured universally, failing to capture the potentially deeper meanings and values that poor people's financial practices represent. In this context both financial inclusion and financial capability require an evaluative framework for the exploration of how and to what degree the ways in which poor people engage with financial services and transactions can improve their wellbeing. This paper examines the potential of Sen's capability approach (CA) as such an evaluative framework. Adopting the CA as an evaluative framework suggests that increasing the availability of financial services is valuable only if the increased range of options allow people to pursue their wellbeing goals. We argue that the capability approach presents a number of characteristics which enable the evaluation of inclusion policy, thereby offering a framework through which financial inclusion is evaluated in terms of its ability to expand people's valued capabilities to achieve wellbeing.
Keywords: 330; Financial capability; financial inclusion; capability approach; wellbeing